HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU SELAMAT PADA WISATAWAN DI PANTAI PARANGTRITIS KABUPATEN BANTUL DIY - Aini, Nurul Samratul; Agustin, Helfi (Universitas Ahmad Dahlan, 2019)
Various health risks can occur in tourism depending on the physical condition of the traveler and the type of trip. Tourists suddenly get sick because of changes in places visited such as altitude, humidity, temperature, or because of an accident. Parangtritis Beach Tourism is a tourist destination with the biggest destination in the Special Region of Yogyakarta (DIY). Parangtritis Beach has an increasing number of visitors annually, of course, accompanied by an increase in the risk of accidents and health problems. The risk of accidents that can occur to tourists is sinking, being hit by ATVs, jeeps and delmans, jellyfish animal bites, food poisoning, air pollution, skin irritation, and others. The purpose of this study was to determine the relationship between knowledge and attitudes with safe behavior on tourists at Parangtritis Beach, Bantul Regency, DIY. This study was an observational study with a cross-sectional or cross sectional study design. The sample in this study were visitors to Parangtritis beach, aged 17-50 years, with 110 respondents. The sampling technique used is accidental side. The instrument in this study was a questionnaire. Data analysis with chi square test. Bivariate analysis shows, sex with healthy and safe behavior (p-value 0.627), age with healthy and safe behavior (p-value 0.911), education with healthy and safe behavior (p-value 0.677), knowledge with healthy behavior and safe (p-value 0.020) and attitudes with healthy and safe behavior (p-value 0.003). There is a relationship between knowledge and attitudes with healthy and safe behavior. There is no relationship between gender, age and education with healthy and safe behavior.